A Novel Method to Estimate the Damage Severity Using Spatial Wavelets and Local Regularity Algorithm (Fracture and Structural Integrity, 2020)
In the process of structural damage detection using continuous wavelet transform (CWT), the perturbation or damage is located by identifying the defects locally in the input signal data.  In this work the damage identification procedure using continuous wavelet transform is developed. This method is studied numerically using a simple beam model. The influence of reduced spatial sampling using fundamental mode shape is investigated in detail. The method is also investigated to ascertain the smallest level of damage identified using strain energy mode shape data.
Keywords: Mode shapes; wavelet analysis; structural health monitoring; Hoelder exponent; Local regularity